Exploring barriers to diversified dietary feeding habits among adolescents in the agrarian community, North West Ethiopia - Agedew, Eskezyiaw; Abebe, Zeweter; Ayelign, Abebe (Frontiers in Nutrition, 2022)
Introduction Adolescence is a critical and neglected age group of the population in any form of nutritional intervention. A comprehensive study that assesses barriers that influence their diversified feeding habit is not well investigated in qualitative approaches. Therefore, this study was conducted to fill this gap by providing evidence on exploring barriers to diversified feeding habits of adolescents in the agrarian community, North West Ethiopia. Objective The aim of the study was to explore barriers to diversified feeding habits of adolescents in the agrarian community, North West Ethiopia. Methods A phenomenological qualitative study design was conducted among adolescents in the age group of 10–19 years, and adults in the age range of 25 to 64 years (representatives of farmers, agricultural, health, and education sectors). We conducted 24 in-depth interviews (12- adolescents, 4-health, 2- agricultural extension, 3-education, and 3-farmer representative) among purposively selected community groups. In-depth interview guides and observation checklist were utilized for data collection. The audio-recorded qualitative data were transcribed word by word into English. Finally, the translated data were exported to ATLAS ti version 7.1 software for thematic analysis based on inductive content analysis. All coded quotations, including memos written throughout the coding process, were then analyzed to identify themes inductively. Results Dietary habit of adolescents in the study area was predominantly plant-based cereals with low protein, vitamins, and mineral contents. Adolescents have limited consumption of fruits, vegetables, and animal source foods. Adolescents with these feeding habits had suboptimal intake of micronutrients and proteins, which are crucial for their rapid growth stage. Individual-level barriers, family-level influence, dietary tradition of community, agricultural practice (poor agroforestry practice of the community, and poor agricultural practice to produce year-round diverse food items), and week multi-sectorial collaboration for nutritional intervention all influenced adolescent dietary habits. Conclusion Multiple layers of barriers influenced the diverse dietary habits of adolescents in the study setting. These multiple and interconnected influences ranged from individual level to multi-sectorial collaboration. Nutritional interventions should be implemented at the individual, family, agricultural, and multi-sectorial levels to improve adolescents’ diverse dietary habits.